Mais je ne suis pas un monument ! - Muriel Prieur (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The luxemburgish art restorer community is not very large. Most of them have, at one or another moment, had to deal with the press. Mostly it stays an ephemeral apparition in the Medias. The project of the restoration of the Consolatrix Afflictorum, Our Lady of Luxemburg, has been largely turned into a national media event. Trough the newspapers, magazines, TV, radio and internet, a major par of the national population knew about it.